Prevalence of sleep disorders in children of a public hospital in São Paulo Prevalência de distúrbios do sono em crianças de um hospital público em São Paulo - Clarisse Potasz; Maria Ligia Juliano; Maria José Varela; Patrícia Gouveia Ferraz; Luciane Bizari de Carvalho; Lucila Fernandes do Prado; Gilmar Fernandes do Prado (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To investigate the prevalence of sleep disorders in a sample of children from a public hospital in the city of São Paulo, Brazil. METHOD: 330 children, who came to the clinical laboratory, were consecutively investigated for sleep disorders, using the sleep disturbance scale for children. Gender, age, and social/economical classification were considered. RESULTS: Sleep disordered breathing (SDB) showed higher prevalence in our sample (55%) than in data found in the literature. Prevalence of sleep hyperhydrosis (SHY) was 27% considering the whole sample. Boys and children in age range 7.1 to 11 years old showed higher prevalence for SDB as well as children belonging to lower social/economic classifications who were also more prevalent for disorders in the transition of sleep-wakefulness. CONCLUSION: Sleep disorders were highly prevailing in our study, mostly SDB and SHY which were exceedingly more prevalent in boys in relation to international literature. OBJETIVO: Investigar a prevalência de distúrbios do sono numa amostra de crianças de um hospital público da cidade de São Paulo, Brasil. MÉTODO: 330 crianças que compareceram ao laboratório clínico foram consecutivamente investigadas para a presença de distúrbios do sono, usando-se a Escala de Distúrbios do Sono para crianças. Foram consideradas variáveis como sexo, idade e classificação sócio econômica. RESULTADOS: Os distúrbios respiratórios do sono (DRS) mostraram alta prevalência (55%) em nossa amostra em relação aos dados encontrados na literatura. A prevalência de hiper hidrose do sono (HHS) foi de 27%. Meninos e crianças da faixa etária compreendida entre 7,1 e 11 anos apresentaram prevalências mais altas para distúrbios respiratórios do sono assim como crianças pertencentes às classificações sócio econômicas mais baixas, que também foram mais prevalentes para desordens da transição sono-vigília. CONCLUSÃO: Os distúrbios do sono foram altamente presentes em nosso estudo, principalmente DRS e HHS, que foram mais prevalentes nos meninos, comparados com a literatura internacional.